Innovation performance through collaborations with public research organizations: Conducting and signaling mechanisms - Bastian Krieger; Stefania Scrofani; Linus Strecke (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2025)
We explore the association between signaling and conducting innovation collaborations with public research organizations and firms' revenues from firm and market novelties. Based on data from the German Community Innovation Survey 2023 and web-based indicators, firms conducting collaboration report higher revenues from market novelties, suggesting their relevance for the performance of more radical innovations. Firms signaling collaboration through website content report higher revenues from firm novelties, suggesting relevance for the performance of more incremental innovations. These findings indicate distinct mechanism in how collaborations with public research organizations relate to innovation performance.
Keywords: O31; O32; O36; 330; University-Industry Transfer; Innovation Performance; Signaling